Development of Science Process Skills Assessment Instruments in Environment Based Practicum on Reaction Rate Material - Nurmala, Nurmala; Sahputra, Rachmad; Rasmawan, Rahmat; Masriani, Masriani; Melati, Husna Amalya (Universitas Pendidikan Mandalika, 2024)
This study aims to produce an Environmental-Based Chemistry Practicum Assessment Instrument for Reaction Rate Material for 11th Grade of MA/ SMA. The development model used in this research is the development model according to Borg and Gall which consists of 4 stages: Potential and Problems, Gathering Information, Product Design, and Design Validation. The development in this study refers to the product produced in the form of an assessment instrument. which is measured until the validity of the expert where the validity aspects are based on the results of the experts' assessment validation questionnaire. The aspects assessed in the product of the environmental-based practicum performance instrument assessment instrument are the feasibility of instructions, content feasibility and language feasibility. The assessment instrument in this content aspect is arranged sequentially according to the practicum procedure. Based on the results of validation by validators, the linguistic aspect obtained a score with a percentage of 93%, then the linguistic aspect is divided into several assessment criteria, including the use of language in accordance with EYD, clarity of instructions and directions and the language used is straightforward and easy to understand Based on the results of validation by validators, the linguistic aspect obtained a score with a percentage of 91%. The validity level of the chemistry practicum performance assessment instrument measured practicum performance in the form of scores 1-4. Determination of the validity of the practicum performance assessment instrument is done by calculating the score given by the validator and analyzing the validator's suggestions and input on the instrument product assessment questionnaire sheet in the form of a check list. The results concluded that the student practicum performance assessment instrument was feasible to use.